Analisis Potensi Diri Anggota Ekstrakurikuler Paskibra di Sekolah Dasar - Neng Melawati; Arsyi Rizqia Amalia; Din Azwar Uswatun (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research aims to analyze the personal potential of extracurricular members in elementary schools. This research uses descriptive qualitative research, qualitative research emphasizes meaning rather than generalizations and the data cannot be resolved using statistical calculations. Qualitative research is research that provides an overview of a phenomenon or situation that occurs. The aim of this research was to determine the personal potential of the extracurricular members of the Paskibra at SDN Kebonjati. The results of the research show that the potential for extracurricular members grows, where the author observes this potential from several indicators, including: Thinking Potential/Intellectual Intelligence, Emotional Potential/Emotional Intelligence (EQ), Physical Potential, and Social Potential. In several of these indicators, the author observes several aspects that prove the growth of personal potential in paskibra members at Kebonjati Elementary School, including: Memory, Creativity, Discipline, Motivation, Maintaining Optimal Physical Condition, Coordination, Building Cohesion, Confident Attitude, and Responsible Attitude.